2020
DOI: 10.4209/aaqr.2020.03.0114
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Exposure to Urban Traffic Related Air Pollutants on Children in Klang Valley, Malaysia

Abstract: Traffic-related air pollutants (TRAPs) are currently increasing due to the increment of vehicle numbers in Malaysia. The emission of pollutants from these vehicles have genotoxic properties that can potentially induce genetic damage in human. In this study, micronuclei assay is used to determine the potential genotoxic exposure by assessing the presence of micronuclei frequency (MN) in buccal cells. The specific objective of this study is to determine the association between TRAPs and frequency of MN among sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The year 2021 was the most recent publication year found and 2012 the oldest. The order of countries that appeared with the most publications on the subject was Italy (Ceretti et al 2014(Ceretti et al , 2020De Donno et al 2016;Idolo et al 2018;Marcon et al 014;Panico et al 2020;Villarini et al 2018), Brazil (Alpire et al 2021;Cavalcante et al 2017;Fleck et al 2014;Silva et al 2015;Sisenando et al 2012), Malaysia (Chokeli et al 2019;Hisamuddin et al 2020;How et al 2014), Mexico (Anguiano-Vega et al 2020Gomez-Arroyo et al, 2013;López Guzmán et al 2017), Argentina (Bernardi et al 2015), and Iraq (Sabah 2021). The results of the characteristics of the included studies are shown in Table 1.…”
Section: General Characteristics Of the Included Studies And Environmental Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The year 2021 was the most recent publication year found and 2012 the oldest. The order of countries that appeared with the most publications on the subject was Italy (Ceretti et al 2014(Ceretti et al , 2020De Donno et al 2016;Idolo et al 2018;Marcon et al 014;Panico et al 2020;Villarini et al 2018), Brazil (Alpire et al 2021;Cavalcante et al 2017;Fleck et al 2014;Silva et al 2015;Sisenando et al 2012), Malaysia (Chokeli et al 2019;Hisamuddin et al 2020;How et al 2014), Mexico (Anguiano-Vega et al 2020Gomez-Arroyo et al, 2013;López Guzmán et al 2017), Argentina (Bernardi et al 2015), and Iraq (Sabah 2021). The results of the characteristics of the included studies are shown in Table 1.…”
Section: General Characteristics Of the Included Studies And Environmental Exposurementioning
confidence: 99%
“…Of the 20 studies, 12 related to children exposed to air pollution (Cavalcante et al, 2017;Ceretti et al 2014Ceretti et al , 2020De Donno et al 2016;Fleck et al 2014;Hisamuddin et al 2020;Idolo et al 2018;Marcon et al 2014;Panico et al 2020;Sabah, 2021;Silva et al 2015;Sisenando et al, 2012); four reported exposures to pesticides (Anguiano-Vega et al 2020;Bernardi et al 2015;Gomez-Arroyo et al 2013;How et al 2014); two about lifestyle (Alpire et al 2021;Villarini et al 2018); and finally, one article researched exposure to arsenic (López Guzmán et al, 2017) and another to a mobile base station (Chokeli et al 2019). The youngest age found in the articles was 7 months while the oldest was 16 years.…”
Section: General Characteristics Of the Included Studies And Environmental Exposurementioning
confidence: 99%
“…SO 2 has been associated with eye irritation, breathing problems, chest pains, heart disease, and respiratory mortality [48]. Inhalation of highly soluble SO 2 will be metabolized into sulfites, which can interrupt DNA synthesis and activate chromosomal abnormality [3].…”
Section: Concentrations Of Air Pollutants In Schoolsmentioning
confidence: 99%
“…HT schools recorded higher average concentrations of air pollutants than LT schools because, in general, air pollutants were significantly higher at the HT schools than the LT schools, due to the high contribution of heavy traffic density. High-traffic density in Klang Valley is partly attributed to developments of housing complexes, underpasses, and flyovers [3]. School children in their indoor and outdoor environments can be the causes of air emissions in the classroom; for example, the movement of children inside and outside of the classroom contributes to the accumulation of PM in the classroom.…”
Section: Concentrations Of Air Pollutants In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation